Peningkatan Hasil Belajar Siswa pada Tematik Terpadu dengan Menggunakan Model Quantum Teaching di Sekolah Dasar - Susanti, Sri; Miaz, Yalvema (Universitas Negeri Padang, 2022)
Describing the improvement of student learning outcomes using the Quantum Tecahing model in integrated thematic learning in grade IV elementary schools is the aim of this study. Integrated thematic learning is learning that uses themes in the learning process. This research method, using classroom action research methods with qualitative and quantitative approaches. Where this research was conducted on the fourth grade students of SDN 03 Pasaman, amounting to 20 people consisting of 12 male students and 8 female students. The results showed an increase in student learning outcomes in integrated thematic learning using the Quantum Tecahing model. From the average value of 73.85% in the first cycle to 87.95% in the second cycle.